2017
DOI: 10.1016/j.ejmech.2017.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Structure–activity relations of rosmarinic acid derivatives for the amyloid β aggregation inhibition and antioxidant properties

Abstract: Amyloid-β aggregation inhibitors are expected to be therapeutic or prophylactic agents for Alzheimer's disease. Rosmarinic acid, which is one of the main aggregation inhibitors derived from Lamiaceae, was employed as a lead compound and its 25 derivatives were synthesized. In this study, the structure-activity relations of rosmarinic acid derivatives for the amyloid-β aggregation inhibitory effect (MSHTS assay), antioxidant properties, and xanthine oxidase inhibition were evaluated. Among the tested compounds,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 26 publications
1
34
0
Order By: Relevance
“…Figure 1 B plots the amount of aggregates estimated from the SD of the brightness of each pixel of a fluorescence microscope image [ 28 , 36 ]. Under similar conditions, Aβ began to aggregate at around 5 h [ 34 ], suggesting that the lag time of SAA aggregation is shorter than that of Aβ. Similar to Aβ, tau and α-synuclein [ 36 ], 3D images of SAA aggregates could be obtained by confocal laser microscopy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 B plots the amount of aggregates estimated from the SD of the brightness of each pixel of a fluorescence microscope image [ 28 , 36 ]. Under similar conditions, Aβ began to aggregate at around 5 h [ 34 ], suggesting that the lag time of SAA aggregation is shorter than that of Aβ. Similar to Aβ, tau and α-synuclein [ 36 ], 3D images of SAA aggregates could be obtained by confocal laser microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…It was subsequently reported that Aβ plaque deposition in RA-fed mice was reduced [ 33 ]. RA also shows high antioxidant activity, and antioxidants with a catechol moiety inhibited the aggregation of various amyloid proteins such as Aβ, tau, and α-synuclein [ 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…As previously described [24], an inhibitory compound, rosmarinic acid (RA), was extracted from Satureja hortensis (summer savory), a spice belonging to the Lamiaceae family. RA has high Aβ aggregation inhibition activity, antioxidant properties, and can also inhibit xanthine oxidase [26]. An aggregation inhibitory test of these proteins using RA was performed, noting that RA inhibited the aggregation of Aβ but not tau.…”
Section: Introductionmentioning
confidence: 99%
“…Several in vitro and animal studies have shown the promise of RA in AD therapy. The experiment by Taguchi et al [ 77 ] using docking simulation and direct binding studies investigated the structural features of RA that allowed it to directly interact with Aβ 1–42 . They have shown that the catechol functional group on the caffeic acid side is an important structural feature for binding.…”
Section: Rosmarinus Acid (Ra) In Admentioning
confidence: 99%
“…One critical structural feature for these compounds both in inhibition of Aβ aggregation and ROS-mediated toxicity is the catechol functional moiety that comes in these compounds in good number ( Figure 2 ). The association between this functional group and anti-AD effects has been established in RA and analogues [ 77 ]. We have also shown that such functional group in phenolic acids as well as in the flavonoids skeleton are optimized for numerous pharmacological effects linked to ROS, metal ions chelation and enzyme inhibition [ 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 ].…”
Section: Summary Of Molecular Mechanisms That Attribute To the Demmentioning
confidence: 99%